1998
DOI: 10.1093/jhered/89.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Genealogical relationships among cultivated avocado as revealed through RFLP analyses

Abstract: Anonymous DNA fragments from the genome of cultivated avocado (Persea americana Mill.) were cloned into a plasmid vector and used to screen a total of 36 cultivars. There is a high level of polymorphism among cultivars allowing all cultivars to be assigned a unique genotype based on 14 genetic loci. A cluster analysis of genetic similarities among cultivars revealed three major clusters that correspond to the three major racial groupings of cultivated avocado. Additional clusters appear to reflect cultivars de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 8 publications
6
34
0
2
Order By: Relevance
“…However, our results indicate that each of these eight species can be recognized by a unique combination of morphological characters. In contrast to previous proposals (Popenoe 1941;Kopp 1966;Williams 1977;Davies et al 1998;Fiedler et al 1998), we determined that the three avocado races differ from each other enough to be considered Persea species, as suggested elsewhere (Bergh and Ellstrand 1987;Scora and Bergh 1990). Zentmyer and Schieber (1992) consider that P. nubigena, P. steyermarkii, and P. zentmyerii, are species different from P. americana.…”
Section: Resultsmentioning
confidence: 74%
“…However, our results indicate that each of these eight species can be recognized by a unique combination of morphological characters. In contrast to previous proposals (Popenoe 1941;Kopp 1966;Williams 1977;Davies et al 1998;Fiedler et al 1998), we determined that the three avocado races differ from each other enough to be considered Persea species, as suggested elsewhere (Bergh and Ellstrand 1987;Scora and Bergh 1990). Zentmyer and Schieber (1992) consider that P. nubigena, P. steyermarkii, and P. zentmyerii, are species different from P. americana.…”
Section: Resultsmentioning
confidence: 74%
“…They also found that the Mexican variety was closely related to P. floccosa Mez. Later, Davis et al (1998) also using RFLPs, found three mayor groups of cultivated avocado and additional clusters placed between these mayor groups, indicating a hybrid origin. In addition, Fielder et al (1998) using randomly amplified polymorphic DNA (RAPD) studied and confirmed three groups representing the three varieties of avocado.…”
Section: Diversitymentioning
confidence: 99%
“…(31) Genetic markers and marker-assisted selection Molecular markers are increasingly being exploited in avocado breeding and genetic analysis. Isozymes were initially used as markers, (77) but recent research has focused on a diverse array of DNA markers, including restriction fragment length polymorphisms (RFLPs), (78)(79)(80)(81) variable numbers of tandem repeats (VNTRs), including minisatellites, (82) and simple sequence repeats (SSRs, or microsatellites). (83)(84)(85)(86)(87) A preliminary analysis of nucleotide sequence diversity in the wild progenitors of cultivated avocado suggests moderate levels of single nucleotide polymorphism (SNP) diversity (y w ¼ 0.0071, where y w is Watterson's diversity statistic (88) ), indicating that SNP discovery will be a valuable source of future markers.…”
Section: Gene Cloning and Estsmentioning
confidence: 99%